Characteristic exposure laser diode at low power the test microorganism strainsin in vitro experiments with photoactivated disinfection system (Эндодонтия Today, 2020)
Dental caries remains one of the major problems in the world of dentistry. Searches for an optimal treatment of caries teeth continue through the introduction of the physico-chemical technologies antibacterial effects on hard tissues of the teeth. Among the new means of influencing the pathogens mentioned photodynamic is infection method of hard dental tissues. This article presents the results of laboratory studies of the effect of the diode laser Lazurit the test strains of microorganisms.